Development of a decision support tool for sustainable renovation – a case study. Issue 1 (11th April 2016) - Malmgren, Linus; Elfborg, Stefan; Mjörnell, Kristina
Abstract : Purpose: – Building owners are encouraged to reduce the energy consumption both in order to contribute to national energy saving goals and to reduce the costs of heating and operation of buildings. However, it is important to pursue the most optimal strategy to achieve cost-effective energy use while maintaining other values. Building managers often do not have the time or expertise to make a proper evaluation of the available options, hence there is a need for practical methodologies for evaluation of renovation alternatives. The paper aims to discuss these issues. Design/methodology/approach: – Renobuild, a systematic approach for evaluating renovation alternatives based on sustainability criteria are under development. It aims to compare renovation alternatives from an environmental, economic and social perspective. To verify the methodology it has been used to evaluate different renovation alternatives for a multi-family apartment building in Sweden. Findings: – The study showed that building managers are provided with a clear comparison between different renovation alternatives from a sustainability perspective. Using Renobuild or similar methodologies may highlight renovation measures which marginally increases the investments, but can lead to significant environmental and social benefits. Research limitations/implications: – So far the methodology has only been tested on a limited number of buildings in Sweden. More buildings will need to be tested for further verification. Originality/value: – Not many tools or methodologies exist which address several aspects of sustainability. Renobuild is a practical methodology that can help building owners to increase focus on sustainability.